2022
DOI: 10.1186/s12935-022-02574-2
|View full text |Cite
|
Sign up to set email alerts
|

Piezo1 promoted hepatocellular carcinoma progression and EMT through activating TGF-β signaling by recruiting Rab5c

Abstract: Background Piezo1 has been revealed to play a regulatory role in vascular development and progression of variety tumors. However, whether and how the progression of hepatocellular carcinoma (HCC) regulated by Piezo1 remains elusive. This study aimed to elucidate the effect and mechanisms of Piezo1 in HCC. Methods The mRNA and protein expression level of Piezo1 in HCC samples and cell lines was determined by qRT-PCR, western blot and immunohistochem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…PIEZO2 , IGFBP2 , and ACVR2A upregulation is associated with the promotion of EMT [ 96 , 97 , 98 , 99 , 100 , 101 ]. PIEZO2 (piezo-type mechanosensitive ion channel component 2) regulates the actin cytoskeleton, and actin remodeling can alter drug response [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PIEZO2 , IGFBP2 , and ACVR2A upregulation is associated with the promotion of EMT [ 96 , 97 , 98 , 99 , 100 , 101 ]. PIEZO2 (piezo-type mechanosensitive ion channel component 2) regulates the actin cytoskeleton, and actin remodeling can alter drug response [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIEZO2 , IGFBP2 , and ACVR2A upregulation is associated with the promotion of EMT [ 96 , 97 , 98 , 99 , 100 , 101 ]. PIEZO2 (piezo-type mechanosensitive ion channel component 2) regulates the actin cytoskeleton, and actin remodeling can alter drug response [ 96 , 97 ]. IGFBP2 (insulin-like growth factor-binding protein 2) promotes cellular proliferation, and its upregulation correlates with chemotherapy resistance [ 98 , 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that Piezo1 can help tumor cell metastasis by promoting EMT ( Gao et al, 2021 ; Wang et al, 2021 ). Piezo1 induces EMT by activating the TGF-β/Smad2/3 signaling pathway through the recruitment of Rab5c ( Li et al, 2022d ). Knockdown of Piezo1 transformes the HCCs from a spindle-like literal morphology to a cobblestone-like epithelial morphology, with a decreased ability of cells to migrate, and the growth of subcutaneous and orthotopic xenograft tumors was also inhibited ( Li et al, 2022d ).…”
Section: Association Of Piezo1 With Tumorsmentioning
confidence: 99%
“…Piezo1 induces EMT by activating the TGF-β/Smad2/3 signaling pathway through the recruitment of Rab5c ( Li et al, 2022d ). Knockdown of Piezo1 transformes the HCCs from a spindle-like literal morphology to a cobblestone-like epithelial morphology, with a decreased ability of cells to migrate, and the growth of subcutaneous and orthotopic xenograft tumors was also inhibited ( Li et al, 2022d ). Moreover, Piezo1 also promotes tumor metastasis by activating the non-Smad pathway of TGF-β.…”
Section: Association Of Piezo1 With Tumorsmentioning
confidence: 99%
“…In liver cancer, Piezo1 is directly correlated with poor clinical outcomes. Piezo1 recruits Rab5c, a small GTPase, promoting hepatocellular carcinoma via TGF-β signaling [ 117 ]. Additionally, Piezo1 is necessary for MAPK and YAP activation and translocation in hepatocellular carcinoma through an independent Hippo signaling mechanism [ 118 ].…”
Section: Mechanoreceptors In Cancermentioning
confidence: 99%